Penguatan Kapasitas Guru Dan Komunitas Belajar SMPN 16 Malang melalui Pendampingan Project Based Learning (PJBL) - Istikomayanti, Yuswa (Kontibusi: Jurnal Kontribusi Kepada Masyarakat, 2025)
Mentorship for educators was conducted as part of a community engagement initiative and research dissemination effort, focusing on the topic of Project-Based Learning (PjBL). The subjects of this community service activity were 45 teachers from SMPN 16 Malang, who had participated in a workshop aimed at strengthening the Pancasila student profile and fostering "Sekolah Penggerak" (driving schools model by Ministry of Education). This collaborative endeavor was established between Tribhuwana Tunggadewi University and SMPN 16 Malang in 2023. The mentorship methodology involved a workshop format, encompassing material presentations, brainstorming discussions, and practical exercises in developing lesson plans. Subsequent to the workshop, practical implementation was undertaken in model classes, specifically in grades 8B and 8G. This activity resulted in a shared understanding among SMPN 16 Malang teachers, enabling them to implement project-based learning as a strategy to enhance student competency outcomes, particularly in collaborative learning skills, critical thinking, and empathy.